Cities and Ports (Ciudades, 2017)
In the present article it is realized a study on the urban integration of the infrastructures and port spaces from an approximation to the process of the relations developed between port and city. A few typical stages are established, of general form, - of unit, of growth, of distancing, of separation and isolation-; we are detaining, specially, in the last one of urban integration of these infrastructures explained from the urban development potentials of them. They are considered to be the causal factors of these recent developments and it is deepened, in spite of the characteristics and proper specificities of every case, in the common aspects of such singular operations. It is attended in a particular way to the Spanish experiences of port transformation, from the relation between infrastructural and urban planning and its evolution. Finally these are valued by some critical balances of its results.
Keywords: ports; city-port relation; urban development potentials; urban integration; infrastructural - urban planning relation.